Relationships Between Traumatic Brain Injury and Illicit Drug Use and Their Association With Aggression in Inmates. (April 2016) - Fishbein, Diana; Dariotis, Jacinda K.; Ferguson, Pamela L.; Pickelsimer, E. Elisabeth
Extensive interviews of correctional inmates in South Carolina (2009-2010) were conducted under a Center for Disease Control and Prevention (CDC) grant. We evaluated the extent to which early traumatic brain injury (TBI) and subsequent illicit drug abuse may conjointly influence development of aggression, controlling for alcohol use, and whether cognitive or emotional dysregulation mediated this relationship. Early TBI predicted greater severity and earlier onset of drug use, and an earlier age at first use predicted greater aggression regardless of the age of TBI. Emotional dysregulation mediated effects of TBI on aggression. The potential to design more targeted treatments for this susceptible population are discussed.